Penerapan Metode Qishah Qur’ani Dalam Pembelajaran PAI Sebagai Upaya Meningkatkan Minat Belajar Siswa Sekolah Dasar - Dhitkya Pradana; Alma Nur Fadilah; Atikah Salma Hidayati; Muhammad Zulfikar; Oktavia Fitriani; Syahidin Syahidin; Muhamad Parhan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Islamic religious education has a significant role in forming individual character. However, Islamic Religious Education learning in schools often faces challenges in attracting students' interest. This article aims to explore and analyze the application of the Qishah Qur'ani method as an effort to increase students' interest in learning in Islamic Religious Education subjects. The research method used in this article is the Systematic Literature Review (SLR) method. The results of the research show that the application of the Qishah Qur'ani method positively contributes to increasing students' interest in learning about Islamic Religious Education. The conclusion of this research provides an optimistic view of the potential of the Qishah Qur'ani method as a vital instrument in building students' interest in learning about Islamic Religious Education.